Identification of fermentative bacteria on local microorganisms of golden snail (Pomacea canaliculata Lamarck, 1822) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Retnowati Y, Katili AS. 2021. Identification of fermentative bacteria on local microorganisms of golden snail (Pomacea canaliculate Lamarck, 1822). Biodiversitas 22: 778-784. Local Microorganisms (LMo) is a fermented liquid containing various microorganisms that potentially act as decomposers and bio-fertilizer. P. canaliculata is one of the rice pests that is a basic ingredient of LMo because of its high protein content. The objective of this study was to determine the types of fermentative bacteria on Local Microorganisms of P. canaliculata. The fermentation of LMo was conducted for 0, 7, 14, and 21 days. Microbial population was determined at 7-day intervals based on the TPC method. Characterization and identification based on polyphasic taxonomy including macroscopic and microscopic morphological characters., Molecular identification was based on 16S rRNA gene sequences. The results showed that LMo of P. canaliculata had a low degree of acidity and tended to decrease during the incubation period, from pH 5.3 to 4.0. Bacterial population tends to increase at 0-14 fermentation days and decreases after 21 days. The isolation results showed that the 3 bacterial isolates namely BFPc-01, BFPc-02, and BFPc-03 were isolated based on morphological differences. The morphological characters of BFPc-01 was milky white color colony, Gram-negative, coccus; BFPc-02 isolate was pink, colony color, Gram-negative, coccus; and BFPc-03 isolate was yellow color colony, bacillus, Gram-positive. The results of molecular characterization based on the 16s rRNA gene sequence showed that BFPc-01 isolate similar to Klebsiella pneumoniae MT604895.1 (99.04%), BFPc-02 isolate closely related to Serratia sp. (100%), and BFPc-03 isolate similar to Microbacterium  sp. (100%).
Keywords: Fermentative, local microorganisms, molecular characterization, Pomacea canaliculata